Arrhythmia in tumor lysis syndrome and associated in‐hospital mortality: A nationwide inpatient analysis. Issue 1 (18th December 2020) - Gangani, Kishorbhai; Fong, Hee K.; Faisaluddin, Mohammed; Lodhi, Muhammad U.; Manaktala, Pritika; Sadolikar, Ashish; Shah, Vraj; Gandhi, Zainab; Abu Hassan, Falah; Savani, Sejal; Doshi, Rajkumar; Desai, Rupak
Abstract: Background: Tumor lysis syndrome (TLS) is a life‐threatening oncologic emergency associated with fatal complications including arrhythmia. The epidemiology and mortality outcomes of arrhythmia in TLS are scarcely studied in the literature. Methods: We used the National Inpatient Sample (NIS) to study the prevalence and outcome of arrhythmia in patients hospitalized with TLS (ICD‐9 code 277.88) from 2009 to 2014. Baseline characteristics, burden of arrhythmia, and pertinent outcomes were analyzed. Multivariable regression analysis was performed to identify the impact of underlying malignancy in predicting TLS‐related mortality. Results: A total of 9034 cases of arrhythmia among 37 861 TLS patients were identified. More than half of the arrhythmia cases (67%) were found among white old (>65) males admitted to large bed size and urban teaching hospitals. Arrhythmic cohort showed higher frequency of comorbidities such as fluid‐electrolyte disturbances, hypertension, congestive heart failure, renal failure, dyslipidemia, diabetes, pulmonary circulatory disorders, chronic pulmonary disease, coagulopathy, and deficiency anemia. The most common malignancies were leukemia, lymphoma, metastatic tumor, and solid tumor without metastasis. We found significantly higher odds of in‐hospital mortality among patients with TLS compared to general inpatient population on unadjusted (OR 9.69, 95% CI: 9.27‐10.13, P < .001) and adjusted (OR 4.62, 95% CI: 4.39‐4.85) multivariable analyses. Overall in‐hospital mortality (32% vs 21.3%), median length of stay (11 days vs 9 days), and hospital charges were higher among arrhythmic than nonarrhythmic patients. Conclusion: With the availability of more advanced cancer therapy in the US, nearly one in four inpatient encounters of TLS had arrhythmia. Arrhythmia in TLS patients was associated with higher odds of mortality and increased resource utilization. Therefore, strategies to improve the supportive care of TLS patients plus timely diagnosis and treatment of arrhythmia are of utmost importance in reducing mortality and health‐care cost. Abstract : A total of 23.9% of (n = 9034) encounters with arrhythmia were identified, out of 37 861 TLS‐related hospitalizations. The trends in the prevalence of arrhythmia were stable with rates ranging from 19.8% to 25.8%, with the highest frequency recorded in 2014 (25.8%) (Figure 1A). Atrial fibrillation (13.6%) was the most common arrhythmia followed by ventricular tachycardia in 2.6% of patients (Figure 1B).